Pharmacy Workplace Wellbeing and Resilience: Themes Identified from a Hermeneutic Phenomenological Analysis with Future Recommendations - Jon C. Schommer; Caroline A. Gaither; Nancy A. Alvarez; SuHak Lee; April M. Shaughnessy; Vibhuti Arya; Lourdes G. Planas; Olajide Fadare; Matthew J. Witry (MDPI AG, 2022)
This study applied a hermeneutic phenomenological approach to better understand pharmacy workplace wellbeing and resilience using respondents' written comments along with a blend of the researchers' understanding of the phenomenon and the published literature. Our goal was to apply this understanding to recommendations for the pharmacy workforce and corresponding future research. Data were obtained from the 2021 APhA/NASPA National State-Based Pharmacy Workplace Survey, launched in the United States in April 2021. Promotion of the online survey to pharmacy personnel was accomplished through social media, email, and online periodicals. Responses continued to be received through the end of 2021. A data file containing 6973 responses was downloaded on 7 January 2022 for analysis. Usable responses were from those who wrote an in-depth comment detailing stories and experiences related to pharmacy workplace and resilience. There were 614 respondents who wrote such comments. The findings revealed that business models driven by mechanized assembly line processes, business metrics that supersede patient outcomes, and reduction of pharmacy personnel's professional judgement have contributed to the decline in the experience of providing patient care in today's health systems. The portrait of respondents' lived experiences regarding pharmacy workplace wellbeing and resilience was beyond the individual level and revealed the need for systems change. We propose several areas for expanded inquiry in this domain: (1) shared trauma, (2) professional responsibility and autonomy, (3) learned subjection, (4) moral injury and moral distress, (5) sociocultural effects, and (6) health systems change.